Peptides as key components in the design of non‐viral vectors for gene delivery. Issue 2 (18th September 2020) - Thomas, Joseph; Punia, Kamia; Montclare, Jin Kim
Abstract: Successful clinical implementation of gene delivery relies on the use of viral or non‐viral based vectors to package and protect the therapeutic nucleic acid. These vehicles must also be able to direct the fate of the cargo once it has entered the cell to ensure that the nucleic acid is functional, and the desired outcome is achieved. Compared to viral vectors, non‐viral vectors have the advantage of incorporating different material types such as lipids, polymers, and peptides to tune overall safety and efficacy. Peptides are especially powerful when used in gene delivery vectors as they are able to increase gene delivery efficacy by introducing new biochemical functionality. This review will discuss the use of peptides as central design components in non‐viral gene delivery vectors. The contribution of the peptide component to the overall functionality of the delivery vehicle will be highlighted, with a focus on peptides as the only vehicle component or peptides in complex assemblies with lipids or polymers. Abstract :